Global health education for the post-pandemic years: parity, people, planet, priorities, and practices - Kathryn H. Jacobsen; Caryl E. Waggett (BMC, 2022)
Abstract Global health degree programs are now offered by institutions of higher education in most world regions. Based on our review of the curricula for many of these programs, we identified five domains that are central to current global health education. "Parity" emphasizes health equity as the ultimate goal of global health. "People" comprises the social, economic, cultural, and political contributors to health and access to medical care for individuals and communities. "Planet" encompasses various aspects of globalization and environmental health that affect population health. "Priorities" and "practices" include the values, data, and tools used to design, implement, and evaluate partnerships, policies, programs, and other global health interventions in countries of all income levels. The pandemic is likely to increase student demand for global health education from the undergraduate through the graduate and professional levels. Our "5 Ps model of global health education" provides a comprehensive framework for the core student learning objectives for global health today. Knowledge of each of these domains is essential for preparing students for meaningful experiential learning and skilled professional practice in global health.